2018
DOI: 10.1002/anie.201803721
|View full text |Cite
|
Sign up to set email alerts
|

NH4Be2BO3F2 and γ‐Be2BO3F: Overcoming the Layering Habit in KBe2BO3F2 for the Next‐Generation Deep‐Ultraviolet Nonlinear Optical Materials

Abstract: KBe BO F (KBBF) is still the only practically usable crystal that can generate deep-ultraviolet (DUV) coherent light by direct second harmonic generation (SHG). However, applications are hindered by layering, leading to difficulty in the growth of thick crystals and compromised mechanical integrity. Despite efforts, it is still a great challenge to discover new nonlinear optical (NLO) materials that overcome the layering while keeping the DUV SHG available. Now, two new DUV NLO beryllium borates have been succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
104
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 215 publications
(123 citation statements)
references
References 42 publications
(41 reference statements)
9
104
0
10
Order By: Relevance
“…With several years of sustained exploration and research, many borates with novel crystal structures or excellent optical properties have been reported. Notable examples include a variety of beryllium borates, such as KBe 2 BO 3 F 2 (KBBF) [2], NH 4 -Be 2 BO 3 F 2 [17], NaSr 3 Be 3 B 3 O 9 F 4 [18], and some berylliumfree borates, such as K 3 B 6 O 10 Cl [19], Ba 4 B 11 O 20 F [20], and A 3 B 3 Li 2 M 4 B 6 O 20 F (A=K, Rb; B=Ba, Sr; M=Al, Ga) [21][22][23][24][25]. Beyond borates, phosphates seem to be a good material system to synthesize the deep-UV NLO materials owing to their short UV cut-off edges, as evidenced by a number of phosphates, such as BaPO 3 Cl (180 nm) [26], Ba 5 P 6 O 20 (167 nm) [27], and LiCs 2 PO 4 (147 nm) [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…With several years of sustained exploration and research, many borates with novel crystal structures or excellent optical properties have been reported. Notable examples include a variety of beryllium borates, such as KBe 2 BO 3 F 2 (KBBF) [2], NH 4 -Be 2 BO 3 F 2 [17], NaSr 3 Be 3 B 3 O 9 F 4 [18], and some berylliumfree borates, such as K 3 B 6 O 10 Cl [19], Ba 4 B 11 O 20 F [20], and A 3 B 3 Li 2 M 4 B 6 O 20 F (A=K, Rb; B=Ba, Sr; M=Al, Ga) [21][22][23][24][25]. Beyond borates, phosphates seem to be a good material system to synthesize the deep-UV NLO materials owing to their short UV cut-off edges, as evidenced by a number of phosphates, such as BaPO 3 Cl (180 nm) [26], Ba 5 P 6 O 20 (167 nm) [27], and LiCs 2 PO 4 (147 nm) [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Our studies propose that three-site aliovalent substitution is af acile route for the discovery of good NLO materials.Noncentrosymmetric (NCS) oxide materials have extensively excited academic interest owing to their probable properties with applications in second-order nonlinear optics (NLO) as well as in pyroelectrics,f erroelectrics,a nd piezoelectrics. [1][2][3][4][5][6] To the best of our knowledge,a ne xcellent second-order NLO material should feature al arge second harmonic generation (SHG) coefficient, ahigh relevant laserinduced damage threshold (LDT), appropriate optical transmittance range,m oderate birefringence for achieving phase matching,and good thermal stability.Inaddition, it should be free of moisture and accessible by af acile synthetic method. [7][8][9] Metal iodates currently attract extensive research interest due to their potential outstanding SHG response.…”
mentioning
confidence: 99%
“…To demonstrate whether the N−H⋅⋅⋅F hydrogen bonds could reduce the growth temperature in this system, we conducted a series of experiments to elucidate the relationship between different kinds of cations and the growth temperature (see Table S5). The results revealed that the growth temperature of the ABIF crystal was 60 °C lower than that of ABi 2 (IO 3 ) 2 F 5 (A=K, Rb, Cs) regardless of the yields, which indicated that hydrogen bonds in ABIF could reduce the growth temperature in this system …”
Section: Figurementioning
confidence: 89%
“…Since NH 4 + possesses a similar ionic radius to K + , it also can be used as an alternative group to alkali ions in situ. Unlike alkali metals, NH 4 + and F − can form strong hydrogen bonds, which are favorable for the physical properties of the crystals and may reduce the growth temperature in this system …”
Section: Figurementioning
confidence: 99%